Nanoparticle‐Based Fluoroionophore for Analysis of Potassium Ion Dynamics in 3D Tissue Models and In Vivo. (5th January 2018) - Müller, Bernhard J.; Zhdanov, Alexander V.; Borisov, Sergey M.; Foley, Tara; Okkelman, Irina A.; Tsytsarev, Vassiliy; Tang, Qinggong; Erzurumlu, Reha S.; Chen, Yu; Zhang, Haijiang; Toncelli, Claudio; Klimant, Ingo; et al.
Abstract: The imaging of real‐time fluxes of K + ions in live cell with high dynamic range (5–150 × 10 −3 m ) is of paramount importance for neuroscience and physiology of the gastrointestinal tract, kidney, and other tissues. In particular, the research on high‐performance deep‐red fluorescent nanoparticle‐based biosensors is highly anticipated. It is found that boron‐dipyrromethene (BODIPY)‐based K + ‐sensitive fluoroionophore FI3 encapsulated in cationic polymer RL100 nanoparticles displays unusually strong efficiency in staining of broad spectrum of cell models, such as primary neurons and intestinal organoids. Using comparison of brightness, photostability, and fluorescence lifetime imaging microscopy, it is confirmed that FI3 nanoparticles display distinctively superior intracellular staining compared to the free dye. FI3 nanoparticles in real‐time live cell imaging are evaluated and it is found highly useful for monitoring intra‐ and extracellular K + dynamics in cultured neurons. Proof‐of‐concept in vivo brain imaging confirms applicability of the biosensor for visualization of epileptic seizures. Collectively, these data make fluoroionophore FI3 a versatile cross‐platform fluorescent biosensor, broadly compatible with diverse experimental models, and crown‐ether‐based polymer nanoparticles can provide a new venue for the design of efficient fluorescent probes. Abstract : Amphiphilic nanoparticles produced from the positively charged polymer and ion‐selective fluoroionophore display remarkable cell staining ability over the broad range of live cell and tissue models: adherent cells, spheroids, organoids, and brain tissue. Using boron‐dipyrromethene (BODIPY)‐based K + ‐sensitive fluorescent red emitting nanoparticles, their utility in neural cell and functional brain imaging is demonstrated.